Myokines in Acromegaly: An Altered Irisin Profile - Mizera, Łukasz; Halupczok-Żyła, Jowita; Kolačkov, Katarzyna; Zembska, Agnieszka; Grzegrzółka, Jędrzej; Jędrzejuk, Diana; Bolanowski, Marek; Daroszewski, Jacek (Frontiers in Endocrinology, 2021)
Introduction: The muscle is an endocrine organ controlling metabolic homeostasis. Irisin and myostatin are key myokines mediating this process. Acromegaly is a chronic disease with a wide spectrum of complications, including metabolic disturbances. Purpose: To examine the influence of acromegaly on irisin and myostatin secretion and their contribution to metabolic profile and body composition. Materials and Methods: In 43 patients with acromegaly and 60 controls serum levels of irisin, myostatin, growth hormone (GH), insulin-like growth factor 1 (IGF-1), parameters of glucose, and lipid metabolism were determined. Body composition was assessed with dual-energy X-ray absorptiometry. Results: The irisin concentration was significantly lower in patients with acromegaly compared to controls (3.91 vs. 5.09 μg/ml, p = 0.006). There were no correlations between irisin and GH/IGF-1 levels. In the study group, irisin was negatively correlated with fasting insulin (r = -0.367; p = 0.042), HOMA-IR (r = -0.510; p = 0.011), and atherogenic factors: Castelli I (r = -0.416; p = 0.005), Castelli II (r = -0.400; p = 0.001), atherogenic coefficient (AC) (r = -0.417; p = 0.05). Irisin and myostatin concentrations were also lower in acromegalics with insulin resistance than without (2.80 vs. 4.18 μg/ml, p = 0.047; 81.46 vs. 429.58 ng/l, p = 0.018, respectively). There were no differences between study group and controls in myostatin concentration. Myostatin levels negatively correlated with GH (r = -0.306; p = 0.049), HOMA-IR (r = -0.046; p = 0.411), and insulin levels (r = -0.429; p = 0.016). Conclusions: Decreased irisin concentrations in acromegaly may suggest impaired hormonal muscle function contributing to metabolic complications in this disorder. However, learning more about the association between myostatin and GH in acromegaly requires further studies. Nevertheless, it appears that myostatin is not critical for muscle mass regulation in acromegaly.